Implementing Reading Aloud to Foster Students' Speaking Skills for Grade Eight at MTSN Kota Palopo - Hasriani; Madehang; Ermawati (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
The aims of this research are twofold: (1) to investigate how the reading aloud technique is applied in enhancing the speaking skills of eighth-grade students at MTsN Kota Palopo, and (2) to assess its effectiveness in improving those skills. The study utilized a pre-experimental method, specifically employing a one-group pre-test and post-test design, to evaluate the impact of the treatment. The research population included 288 eighth-grade students, from which a single class—Class C with 32 students—was purposively selected due to their relatively better speaking ability compared to other classes. The results indicated that the use of reading aloud as a teaching strategy had a positive effect on students’ speaking development. This approach incorporated structured oral practice through reading aloud and interactive question-and-answer sessions, targeting the enhancement of accuracy, fluency, and clarity in speech. The mean score from the pre-test was 24.43, categorized as